Alan Cowey. 28 April 1935—19 December 2012. (28th July 2019) - Passingham, Dick
Abstract : Alan Cowey's primary interest was in the way in which we interpret the visual world. This led him to study not only the early visual areas but also the inferotemporal and parietal cortex with which they are connected and the further projections into the eye field in the prefrontal cortex. His research interests were wide, covering colour vision, attention, visual neglect and the anatomical basis of the visual abilities that can be spared after a lesion in the primary visual cortex. Alan spent over 40 years at the University of Oxford, where he was involved in many initiatives and served on many committees, playing many important roles in the development of neuroscience as an interdisciplinary field of research.